Estados estacionários de partículas sem spin em potenciais quadrados - Cardoso, Tatiana R. [UNESP]; de Castro, Antonio S. [UNESP] (My University, 2008)
The one-dimensional Klein-Gordon equation is investigated with the most general Lorentz structure for the external potentials. The analysis and calculation of the reflection and transmission coeffifients for the scattering of particles in a square potential, with an arbitrary mixing of vector and scalar couplings, reveal circumstances which conflict with the predictions from nonrelativistic quantum mechanics. It is shown that such anomalous scatterings are mediated by antiparticle bound states, even if the incident particles have low energies. The analysis of bound states also reveals surprising results, remarkable is the inhibition of the Schiff-Snyder-Weinberg effect due to the presence of a scalar coupling. Copyright by the Sociedade Brasileira de Física.
Stationary states of spinless particles in square potentials
Keywords: Klein's paradox; Klein-Gordon equation; Pair production; Schiff-snyder-Weinberg effect; Spinless particles